If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 1 + -2n + 55 Reorder the terms: 6 = 1 + 55 + -2n Combine like terms: 1 + 55 = 56 6 = 56 + -2n Solving 6 = 56 + -2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '2n' to each side of the equation. 6 + 2n = 56 + -2n + 2n Combine like terms: -2n + 2n = 0 6 + 2n = 56 + 0 6 + 2n = 56 Add '-6' to each side of the equation. 6 + -6 + 2n = 56 + -6 Combine like terms: 6 + -6 = 0 0 + 2n = 56 + -6 2n = 56 + -6 Combine like terms: 56 + -6 = 50 2n = 50 Divide each side by '2'. n = 25 Simplifying n = 25
| 7-3x-4+x= | | 8+x=-x+4 | | 24-13n=-17n | | x-0.2x=412800 | | 20-4y=0 | | 6p+21=15p+60 | | 27-3.6x=8.4+23.7x | | 6-2(x+2)=16 | | 15x^2+22x=(-8) | | -n+19=7(n-3) | | 22-13=3(x-7) | | 6p+21=15p+4 | | 27-3.6x=8.4+23.7 | | 7=9-y | | 26+3x=6x | | 0.8x+8.5=4.1 | | -(3z+4)=6z-3(3+2) | | 6w^2=3w+3 | | 4n+9=56 | | X=ax-bx | | -6(x+8)-44=7-45 | | x+3x/2=30 | | j+10=-j | | 3x-25=x+55 | | 4m-4=2(2m+4) | | 29+3y-4=13y-11-4y | | 2y+2=4 | | C=ax-bx | | 9x=3(8x+25) | | -3x-(-24)=24 | | 5.4t+14.6-10.1t=12.8-3.8t-0.6 | | -2x+5=x-4 |